Awake nasotracheal intubation under bronchoscopic guidance and anesthetic management in a patient undergoing excision of an endotracheal mass: A case report. Issue 45 (12th November 2021) - Kim, Jonghae; Park, Bum Young; Lim, Jung A.
Abstract: Rationale: The main challenge facing anesthesiologists during endotracheal mass resection is securing effective airway management during surgery. It is important to select an airway intubation and airway maintenance method according to the patient's condition and the characteristics of the mass. Patient concerns: A 74-year-old woman with aggravated dyspnea for 1 year was scheduled to undergo endotracheal mass excision under general anesthesia. Diagnosis: The mass was 4 × 3 × 3 cm ovoid-shaped, and located 4 cm above the carina, occupying 41% of the tracheal lumen in a preoperative chest computed tomography and bronchoscopy. Interventions: After preparing extracorporeal membrane oxygenation in case of the inability to ventilate and intubate, we attempted awake bronchoscopy-guided nasotracheal intubation using a reinforced endotracheal tube with an inner diameter of 5.5 mm and outer diameter of 7.8 mm after a translaryngeal block. The tube was passed around the mass without resistance and placed right above the carina. With the tube pulled back above the mass, another tube was introduced from the opened trachea below the mass to the right main bronchus. Following the resection of the tracheal portion containing the mass, the posterior wall of the remaining trachea was reconstructed. The tube placed in the right main bronchus was removed and the tube in the upper trachea was introduced right above the carina. The patient's head was kept flexed once the anastomosis of the trachea was completed, and the surgery ended uneventfully. Outcomes: The mass was confirmed as schwannoma by histopathological finding. The patient was discharged from the hospital on the 6 th postoperative day without complication. Lessons: Awake bronchoscopy-guided intubation is a safe airway management method in patients with an endotracheal mass. Close cooperation between anesthesiologist and surgeon, and preparation for airway management before surgery is essential. It is necessary to establish alternative plans that can be implemented in the case that intubation and ventilation are not possible.